2001
DOI: 10.7589/0090-3558-37.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity—mortality Factors and Survival of an Urban Coyote Population in Arizona

Abstract: The health of coyotes (Canis latrans) in urban areas has not been studied. Our objectives were to assess the health of coyotes in Tucson (Arizona, USA) by determining the prevalence of antibodies to selected pathogens, estimating survival rates, and identifying sources of mortality. We drew blood from 22 coyotes to evaluate the prevalence of heartworm (Dirofilaria immitis) antigens, and antibodies to canine distemper virus (CDV), infectious canine hepatitis (ICH), canine parvovirus (CPV), and seven serovars of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
50
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 23 publications
7
50
1
Order By: Relevance
“…McCue and O'Farrell (1988) reported CDV antibodies in 0-14% of the kit foxes sampled in California. We found that levels of CDV antibodies increased with age among both species, similar to results among coyotes in Texas (Guo et al, 1986), Wyoming (Gese et al, 1997), Arizona (Grinder and Krausman, 2001), and Utah (Arjo et al, 2003). The higher prevalence of CDV antibodies in adults may be a result of adults being more likely to survive exposure or adults having a longer exposure period to the virus and developing a persisting titer (Gorham, 1966;Green et al, 1984).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…McCue and O'Farrell (1988) reported CDV antibodies in 0-14% of the kit foxes sampled in California. We found that levels of CDV antibodies increased with age among both species, similar to results among coyotes in Texas (Guo et al, 1986), Wyoming (Gese et al, 1997), Arizona (Grinder and Krausman, 2001), and Utah (Arjo et al, 2003). The higher prevalence of CDV antibodies in adults may be a result of adults being more likely to survive exposure or adults having a longer exposure period to the virus and developing a persisting titer (Gorham, 1966;Green et al, 1984).…”
supporting
confidence: 66%
“…The prevalence of CPV antibodies among San Joaquin kit foxes (V. macrotis mutica), a close relative of the swift fox (Mercure et al, 1993), ranged 67-100% in California (McCue and O'Farrell, 1988). The prevalence of CPV antibodies in coyotes from other western states (Arizona, Idaho, Utah, and Wyoming) was generally Ͼ70% (Thomas et al, 1984;Gese et al, 1997;Grinder and Krausman, 2001;Arjo et al, 2003). A high prevalence of antibodies is associated with a highly contagious, but nonfatal, infection, because prevalence is measured among survivors (Thomas et al, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Holzman et al (1992), Gese et al (1997), and Grinder and Krausman (2001) found 64, 100, and 100%, respectively, of coyotes antibodypositive for CPV but did not investigate shedding. Miller et al (2009) did not test for antibodies but found one in 36 coyotes from South Carolina to be shedding parvovirus particles on electron microscopic examination of feces.…”
mentioning
confidence: 95%
“…In Arizona 25% prevalence of CDV antibody was reported in foxes (Vulpes spp.) and 27% in coyotes (Canis latrans) (Miller et al, 2000;Grinder and Krausman, 2001).…”
Section: Canine Distemper (Cd) Is Caused By Amentioning
confidence: 99%